Exploring identity achievement amongst senior high school students. - Macheka, Anesu T. (Midlands State University, 2017)
The purpose of the study was to highlight on the levels of identity achievement amongst senior high school students, the study wanted to unveil underlying fundamental aspects of identity amongst senior High School students in order to assist with behaviour modification as identity is a key player in behaviour outcomes. The research wanted to address mainly the issue of lack of identity amongst senior high school students in Gweru, lack of identity was manifested through maladaptive behaviours which were very rife amongst senior high school students. Theorists like Erikson indicate that individuals who are in their senior year high school are at the stage where they should have committed to an identity, but however the researcher noted that there were a number of behaviour problems amongst senior high school students and hence the need to measure their level of identity achievement. The research made use of the quantitative research approach and adopted the descriptive research design. The sample used in the research were 120 senior high school students at Thorn hill high school in Gweru and the systematic random sampling technique was used for selection. Data collected was analysed by the use of SPSS and Microsoft Excel, and the main findings were that female students were higher in terms of identity achievement compared to male students. The research also indicated that identity styles are dependent on a number of variables which include gender, religion and socio-economic background.